Behavioral Treatment of Sleep Problems using Wake-Time Fading with Individuals with Autism: A Brief Report. (17th February 2023) - Hausman, Nicole L.; Falligant, John M.; Bednar, Molly K.; Carver, Ashley N.; Connaughton, Kaitlyn
ABSTRACT: Difficulties with sleep, such as delayed onset, night waking, and early waking, are pervasive among individuals with developmental disabilities and autism. Interventions that seek to improve sleep outcomes are particularly useful when these individuals have experienced extended hospitalizations where low activity levels and decreased exposure to light–dark cycles maintain or increase disturbance in sleep patterns. The current study examines the effects of wake-time phase advances on the sleep patterns of a 16-year-old male and 17-year-old female, both of whom presented with significant sleep disturbance, autism, developmental delays, and severe problem behavior in a hospital-based setting. For both individuals, clinically significant increases in appropriate sleep and decreases in latency to sleep were observed throughout the course of their admission as a result of wake-time phase advances. Together, these results replicate and extend limited research in this area by using behavioral interventions to decrease disrupted sleep in inpatient contexts.